Diabetic retinopathy prevention and treatment options - Santiago, Gerardo Garcia; Gonzalez, Guillermo Avalos; Velazquez, Jose M. Huerta; Torres, Jose Maria Zepeda; Curriel, Alexa Jimenez (International Journal of Advances in Medicine, 2023)
The objective of this review article was to mention the prevalence and risk factors for diabetic retinopathy to occur. Also, mention and compare the best ways to prevent this complication. Adding also a comparison of the best currently available treatments for diabetic retinopathy. Diabetic retinopathy is the first cause of visual impairment in working-age adults worldwide. Duration of diabetes is a major risk factor associated with the development of diabetic retinopathy. Due to the large number of patients with type 2 diabetes, this group comprises a larger proportion of the disease burden in patients with visual impairment from diabetic retinopathy compared to patients with type 1 diabetes. Diabetic retinopathy is the most common cause of visual impairment and blindness in patients aged 20-74 years. Approximately 80% of the patients with type 1 diabetes will develop retinopathy after 15 years after the onset of the pathology. In the case of type 2 diabetes will develop retinopathy after 30 years of history with the disease. Some important factor that can accelerate the process is the use or not of insulin for treatment. The most important for the treatment of diabetic retinopathy is the prevention of the diabetes in healthy people that have the risk factor to develop this pathology. The best options of treatment continued to be the combination of anti-VEFG/panphotocoagulation depending the stage of the complication. Improvement of the early detection of this type of microvascular complication for give them an early treatment and improve the evolution in positive way. We believed that is need to investigate more techniques for early detections of microvascular complications of diabetes mellitus, like imagen or biomarkers.